EMPOWERING INDONESIAN MIGRANT WORKERS’ FAMILIES IN MALAYSIA THROUGH USED COOKING OIL-BASED SOAP MAKING TRAINING AND LITERACY ENHANCEMENT FOR PARENTS AND CHILDREN - Zulys, Agustino; Bintari, Dini Rahma; Maulana, Ary; Yani, Sela Vivi; Takhwifa, Famila (Ikatan Dosen Menulis, 2026)
Indonesian Migrant Workers (PMI) families in Malaysia face layered challenges such as limited access to formal education services for their children and economic vulnerability for the parents. This community service aims to enhance the economic capacity of households through the utilization of used cooking oil waste and the optimization of the learning and literacy quality of PMI children at the Sanggar Bimbingan (SB) Meru, Klang, Selangor. The implementation method consists of stages of problem identification, data collection, data analysis, intervention priority setting, goal setting, program execution, evaluation, and adjustment. Implementation of a multidimensional program that includes training in making bar soap from used cooking oil, children’s literacy classes, sensorimotor stimulation, teacher training, and psychoeducational parenting. The program is implemented in collaboration with Universiti Teknologi Malaysia (UTM) and the Biman Foundation to ensure the program’s reliability. The impact measurement results are assessed qualitatively and quantitatively. Quantitative evaluation using pre-test and post-test instruments shows a significant increase in knowledge across all target groups. Parents’ understanding of soap making increased by 51,19%, teacher’s understanding after attending the literacy class improved by 31,04%. Beneficiary satisfaction evaluation scored an average of 4.49 out 5.00. Long-term sustainability is supported by the provision of modulus and self-education kits, backed by regular online monitoring. Through the framework of community empowerment, this program has successfully strengthened the economic, social, and educational dimensions for marginalized PMI communities.